Best practices of promoting teacher professional development among principals of cluster secondary schools towards realization of education blueprint 2013 – 2025 Malaysia - Salleh, Mohamad Johdi; Hatta, Muhammad (2017)
The study examines the best practices of promoting teacher professional development among principals of cluster secondary schools Malaysia. The Principal Instructional Management Rating Scale (PIMRS) formulated, modified and adapted by Hallinger and Murphy (1985), Leithwood (1999), Latip (2006), Hatta (2010) and McCarley, Peters, & Decman (2016) was used as the data collection instrument through survey questionnaire. The researcher employed descriptive statistical procedures involving frequency count, percentage distribution, and, means to analyze the data collected. There were 871 respondents of different genders, ethnics, type of schools, and, position of responsibilities at schools were participated. The finding of the study indicated that the highest score in Promoting Teacher Professional Development among Principals of Cluster Secondary Schools Malaysia according to Principals and Teachers Perceptions was a statement ‘Set aside time at faculty meetings for teachers to share ideas on instruction or information from in-service activities’ which as high as 300 respondents (34.4%) selected ‘Always’, 340 respondents (39.0%) selected ‘Frequently’, 192 respondents (22.0) selected ‘Rarely’, 30 respondents (3.4%) selected ‘Seldom’, and, only 9 respondents (1.0%) selected ‘Never’. It is hoped that this research would provide useful findings to effectively assist the process of promoting professional development enhancement among principals and teachers of all schools to improve students' academic performance in achieving the first class human capital who are compatibly excellent nationally and internationally as stipulated in the purpose of establishing the cluster schools by the Ministry of Education Malaysia and realization of Vision 2020 and the Malaysian Education Blueprint 2013-2025 towards global excellence.